2016
DOI: 10.5301/tj.5000587
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Multi-institutional Clinical Trial on a New Mixed Beam RT Scheme of IMRT on Pelvis Combined with a Carbon Ion Boost for High-risk Prostate Cancer Patients

Abstract: The present clinical trial aims at improving the current treatment for high-risk prostate cancer, evaluating safety and feasibility of a new RT mixed-beam scheme including photons and carbon ions. Encouraging results are coming from carbon ion facilities worldwide on the treatment of different tumors including prostate cancers. Carbon ions combine physical properties allowing for high dose conformity and advantageous radiobiological characteristics. The proposed mixed beam treatment has the advantage to combin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…The inclusion criteria were men with pathologically confirmed localized prostate cancer who received CIRT as the radical treatment. Patients with visceral or bone metastases [10], pelvic nodes metastases [11], postoperative radiotherapy [4], and recurrence after either surgery or radiotherapy [7] were excluded. Finally, 64 eligible patients participated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were men with pathologically confirmed localized prostate cancer who received CIRT as the radical treatment. Patients with visceral or bone metastases [10], pelvic nodes metastases [11], postoperative radiotherapy [4], and recurrence after either surgery or radiotherapy [7] were excluded. Finally, 64 eligible patients participated in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The NCT02672449 is a prospective, multicentric, phase II open-label trial that might provide novel insights on a new mixed beam RT scheme of a carbon ion boost followed by pelvic photon RT ( 76 ), and details about this ongoing trial are reported in Table 1 . Overall, data about CIRT in HR setting seems encouraging and could provide novel insight for the treatment of these patients.…”
Section: New Scenariosmentioning
confidence: 99%
“…4) The higher RBE and sharper lateral fields of CIRT, permitting biologic and physical dose escalation, should improve local control more than might be expected with photon‐based or proton‐based SBRT . 5) Hypoxia and other mechanisms of radiation resistance thought to confer resistance to photon‐based EBRT may be overcome with CIRT . And 6) intermediate endpoints, such as prostate‐specific antigen nadir and/or time to metastatic disease, could be used to support the viability of CIRT …”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…40 5) Hypoxia and other mechanisms of radiation resistance thought to confer resistance to photon-based EBRT may be overcome Cancer December 1, 2018 with CIRT. 27,[49][50][51] And 6) intermediate endpoints, such as prostate-specific antigen nadir and/or time to metastatic disease, could be used to support the viability of CIRT. 38,40,52,53 Patients with prostate cancer (including those from the United States) initially would receive treatment with 4 or 5 fractions of SBRT using photons (x-rays) versus protons versus CIRT (with photons considered the standard to which the others are compared), as noted above.…”
Section: Cancer Sites Suitable For Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation